2017
DOI: 10.3892/mmr.2017.7586
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-186 targets IGF-1R and exerts tumor-suppressing functions in glioma

Abstract: Glioma is the most common malignant brain tumor in adults and represents one of the most aggressive and life‑threatening types of cancer in humans. Increasing studies have revealed that microRNAs are abnormally expressed in various types of human cancer, and have oncogenic or tumor suppressive roles, which depend primarily on the type of cancer. The present study aimed to investigate the expression level and effects of microRNA‑186 (miR‑186) on glioma, and its underlying molecular mechanism. Reverse transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…IGF-1R overexpression reversed the suppressive effects induced by SNHG11 knockdown on the malignant phenotypes of PCa cells. Previous studies have also demonstrated that IGF-1R plays an oncogenic role in several types of cancer, including PCa ( 28 ), bladder cancer ( 29 ), colorectal cancer ( 26 ) and glioma ( 30 ). Similarly, the data of the present study also suggested that IGF-1R may act as an oncogene in PCa.…”
Section: Discussionmentioning
confidence: 98%
“…IGF-1R overexpression reversed the suppressive effects induced by SNHG11 knockdown on the malignant phenotypes of PCa cells. Previous studies have also demonstrated that IGF-1R plays an oncogenic role in several types of cancer, including PCa ( 28 ), bladder cancer ( 29 ), colorectal cancer ( 26 ) and glioma ( 30 ). Similarly, the data of the present study also suggested that IGF-1R may act as an oncogene in PCa.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, miRNAs play a vital role in tumorigenesis, biological development, organogenesis, apparent regulation, and metabolism (27,28). Previous studies have shown that miR186 targeted IGF-1R in glioma (29), and Yin Yang 1 (YY1) and cyclin dependent kinase 6 (CDK6) in prostate cancer (30). In addition, PTTG1 (31), P2X7 (32), FOXO1 (33), AKAP12 (34,35) and Caspase-10 (36) have also been identified as direct targets of miR186 in different types of cancer in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies focused on IGF1R have identified that IGF1R expression is associated with numerous types of tumors, including glioma (2629). IGF-1R has also been confirmed as a direct target gene of numerous microRNAs that are associated with glioma proliferation and invasion (27,30). The IGF1R pathway has been reported to be associated with treatment resistance in glioma (29).…”
Section: Discussionmentioning
confidence: 99%